Implikasi Hukum Terhadap Hak Pekerja Harian Lepas di Era Digital: Perspektif Hukum Ketenagakerjaan - Wildan, Ahmad; Hayat, Gian Muzakir; Podungge, Khalisyah Amara (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The digital era has changed many aspects of life, including the world of work, with the emergence of new work models such as working from home and remote work. The three main factors driving this change are technological disruption, technological adaptation, and work transformation, which have been amplified by the pandemic. Freelance work is becoming increasingly common, but is often not accompanied by adequate regulations to protect workers' rights. This research aims to analyze how labor regulations can be adapted to accommodate the new realities of the digital era and provide better protection for freelance workers. The method used is descriptive analysis with a normative juridical approach, examining labor regulations in Indonesia. The research results show that although technological advances bring benefits, many freelancers face legal status protection and lack of rights protection. More effective and comprehensive regulations are needed, as well as cooperation between governments, employers, academics and legal experts to create a fairer and more sustainable work environment.